VD_FINDINFO Jug / 2023 / 314 vom 8. September 2022 - VD Tribunal cantonal (2022)
VOLDROIT PÉNAL, RECEL, PLAINTE PÉNALE, FUSION, PARTIE CIVILE, PLAIGNANT, APPELCPP, RECOURSCPP, ENQUÊTE PÉNALE | 139 CP, 160 ch. 1 CP, 160 ch. 2 CP, 29 al. 2 Cst., 10 CPP (CH), 104 CPP (CH), 121 al. 2 CPP (CH), 135 CPP (CH), 389 CPP (CH), 393 CPP (CH), 398 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH)